Understanding what Drives College Football Season Ticket Renewals - Chris Greenwell; Adam Cocco; Nels Popp (Journal of Applied Sports Management, 2026)
Recent changes in intercollegiate athletics have significantly impacted the economics of college football. Heightened competition and increased operational costs have necessitated greater revenue generation through ticket sales, as ticket sales contribute a significant amount of revenue to college athletic department’s budgets. Therefore, this study utilizes self-determination theory to investigate factors influencing football season ticket holders’ intentions to renew. Employing a survey of 6,777 season ticket holders from 11 schools competing in an NCAA Division I Power 4 conference, the study identifies significant predictors of renewal intentions based on intrinsic (Team Direction, Game Day Experience, and Sense of Being Valued) and extrinsic factors (Affordability, Seat Location, Season Ticket Discounts, and Season Ticket Holder Perks). Findings reveal that intrinsic motivations such as Team Direction and Game Day Experience are significantly associated with renewal intentions, emphasizing the importance of engagement and appreciation for enhancing fan loyalty and sustaining revenue streams.
Keywords: season ticket renewals; college football; intrinsic motivation; extrinsic motivation